Antenatal corticosteroids administration on mortality and morbidity in premature twins born at 25∼34 gestational weeks: A retrospective multicenter study. (October 2020) - Kong, Xiangyong; Xu, Fengdan; Wang, Zizhen; Zhang, Shan; Feng, Zhichun
Abstract: Objective: To evaluate the effects of antenatal corticosteroids (ACS) administration on mortality and major neonatal complications in early life of preterm twins. Study Design: This study retrospectively enrolled 1 662 twins delivered at 25∼34 +6 gestational weeks in China from January 2013 to December 2014. They were divided into ACS group and no-ACS group according to weather their mothers received ACS or not. Moreover, they were subgrouped as 25∼27 +6 and 28∼34 +6 gestational week groups. Multivariable logistic regression was used to analyze the effects of ACS on the incidence of mortality and major morbidities. Results: A total of 910 neonates (54.8 %) received one or more doses of ACS, and 752 neonates (45.2 %) did not receive any ACS. No significant difference in infant mortality was observed between the ACS and no-ACS groups ( P = 0.321). The ACS group had decreased incidence of respiratory distress syndrome (RDS) and mild RDS compared with the no-ACS group (both P < 0.05 ). There were no significant differences in the incidence of bronchopulmonary dysplasia, intraventricular hemorrhage, necrotizing enterocolitis, retinopathy of prematurity, patent ductus arteriosus, sepsis and severe RDS between the two groups (all P > 0.05). The subgroup analysis showed that the incidence of RDS was lower in the ACS group than in the no-ACS group ( P = 0.036) at 28∼34 +6 weeks. However, the incidence of mild ROP was higher in the ACS group than that in the no-ACS group ( P = 0.047) at 25∼27 +6 weeks. Multivariable logistic regression analysis demonstrated a decreasing risk of RDS ( aOR = 0.661, 95 % CI :0.506−0.863, P = 0.002) after adjusting the gestational week, birth weight, small for gestational age, delivery mode, 5 min Apgar score, and maternal perinatal complications. Conclusion: In twin preterm infants, ACS administration is associated with a reduced risk of RDS. However, our data suggest that it may not have a beneficial effect on mortality and other short-term morbidities.